The effectiveness and safety of amisulpride in Chinese patients with schizophrenia: An 8‐week, prospective, open‐label, multicenter, single‐arm study. (28th March 2016) - Liang, Ying; Cao, Changan; Zhu, Cheng; Wang, Chuanyue; Zhang, Congpei; Dong, Fang; Yang, Fude; Deng, Hong; Yu, Jingjie; Tang, Jisheng; Su, Lei; Xin, Limin; et al.
Abstract: Introduction: This study evaluated the effectiveness and safety of amisulpride in Chinese schizophrenia patients. Methods: A multicenter, single‐arm Phase IV study (NCT01795183). Chinese patients with schizophrenia received amisulpride for 8 weeks. The primary endpoint was ≥50% decrease in Positive and Negative Syndrome Scale total score from Baseline to Week 8. Results: A total of 316 patients were enrolled; 295 were included in the effectiveness analysis; 66.8% (197/295) achieved ≥50% decrease in Positive and Negative Syndrome Scale total score from Baseline to Week 8. Nine patients discontinued treatment because of adverse events. Discussion: Amisulpride had clinical effectiveness and was relatively well tolerated in Chinese patients with schizophrenia.